Development of Android Application for Automated Water Irrigation System and Crop Suggestion Based on Analysis of Data: Enhancing Crop Production and Resource Management through Smart Irrigation and Data Analysis (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Today the biggest contributor to the GDP in India is Agriculture Sector. So there is need to improve the facilities provided to the farmers to increase the crop production. There are some Problems in farming which cannot be solved by the farmer such as Exact water required by the land, nutrients available in soil. Whereas we can overcome these problems by using embedded system which consist of Raspberry Pi, Aruduino Uno, DHT 11 Temperature sensor, moisture sensor. So using this devices we can build a system which can sense the data or parameters from the soil then that data is analysed with the help of Raspberry Pi and ultimately provide crop suggestion and also used in automatic water irrigation. This system also includes Android interface with simple understandable form.